Ketahanan Keluarga Pancasila Dalam Menguatkan Solidaritas Kebangsaan Generasi Muda - Nisa Wening Asih Sutrisno; Inggar Saputra (Proceeding of the International Conference on Global Education and Learning, 2025)
The vulnerability of the younger generation to negative exposure to new media (internet and social media) has the potential to weaken national resilience, especially the aspect of family resilience. Family resilience as a fundamental element is disrupted by negative broadcasts, the rise of hate speech and information (fake news and misleading narratives) that are widely found in new media. For this reason, it is necessary to strengthen national solidarity through the idea of ​​forming Pancasila family resilience that protects the younger generation from the destructive threats of social media. This study aims to determine the extent to which Pancasila family resilience can strengthen the spirit of national solidarity of the younger generation. The study used a literature study method with a qualitative approach. Data collection techniques used primary and secondary sources with data collection techniques using data triangulation. The results of the study stated that (1) The threat of weakening national values ​​arises from digital developments marked by the rise of new media in the form of the internet and social media; (2) The negative influence of new media appears in negative video broadcasts, the phenomenon of hate speech and misleading narratives, and fake news that creates social unrest in society; (3) The concept of Pancasila family resilience is needed to strengthen the spirit of national solidarity and prevent the negative impacts of new media among the younger generation. The conclusion of the research is that the concept of Pancasila family resilience is expected to be able to encourage the spirit of Pancasila in preventing various negative impacts of the digital technology phenomenon, especially the negative influence of new media on the spirit of nationalism among the young generation of Indonesia.